Method for relieving electric field assisted rapid connection residual stress of yttrium oxide transparent ceramic and metal

In the electric field assisted rapid connection between yttrium oxide transparent ceramics and metals, the intermediate layer material is prepared by using magnetron sputtering method, the thickness and type are adjusted, and the thermal expansion coefficient is gradually transitioned, and the residual stress problem caused by mismatch of thermal expansion coefficients is solved, and the residual stress problem is achieved. High strength and high quality connection.

CN119143519AActive Publication Date: 2024-12-17SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310708065.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-15
Publication Date
2024-12-17
Estimated Expiration
2043-06-15

AI Technical Summary

Technical Problem

In the electric field-assisted rapid connection between yttrium oxide transparent ceramics and metals, the residual stress caused by mismatch in the thermal expansion coefficient is too large, which reduces the quality and reliability of the joint.

Method used

Design an intermediate layer connection material, including hard metal, intermediate layer or composite intermediate layer, prepared by magnetron sputtering method, adjust the thickness and type of intermediate layer, gradient transition thermal expansion coefficient, reduce residual stress, and excite oxygen defects through DC electric field Achieve quick connection.

Benefits of technology

It effectively relieves residual stress during the connection process, improves connection strength and mass, shortens connection time, reduces the required current density, and improves the mechanical properties of the joint.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143519A_ABST
    Figure CN119143519A_ABST
Patent Text Reader

Abstract

The invention relates to a method for relieving electric field assisted rapid connection residual stress of yttrium oxide transparent ceramic and metal. The intermediate layer connecting material for relieving the electric field assisted rapid connection residual stress of the yttrium oxide transparent ceramic and the metal comprises a hard metal intermediate layer, a composite intermediate layer or a soft metal intermediate layer from the side of the yttrium oxide transparent ceramic; the hard metal intermediate layer is selected from Ti and Cr, the soft metal intermediate layer is selected from Ni and Al, and the composite intermediate layer is selected from Ti / Ni, Ti / Al, Cr / Ni or Cr / Al.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of dissimilar material connection, and in particular relates to an intermediate layer connection material and method for alleviating residual stress in electric field-assisted rapid connection of yttrium oxide transparent ceramic and metal. Background Art

[0002] Currently, transparent ceramics with high optical quality are widely used in laser, military, and medical fields. Yttrium oxide (Y2O3), among them, has great application value in high-temperature windows, infrared headgear, luminescent media, and the semiconductor industry due to its stable performance and high transmittance in the 0.23μm to 8.0μm range. However, the high brittleness and poor processability of yttrium oxide transparent ceramics limit their engineering applications. Considering the complementary relationship between ceramics and metals, joining yttrium oxide transparent ceramics to metals is an effective approach to overcome these shortcomings. Currently developed transparent ceramic-to-metal joining technologies mainly rely on adhesive bonding, brazing, and diffusion bonding. Inorganic or organic adhesives used for bonding ceramics to metals tend to soften and fail at high temperatures, limiting their usable temperature range. Brazing is convenient and efficient, but its practical operating temperature range is relatively low. Diffusion bonding offers the advantages of high joint strength and high-temperature resistance, but the long joining time degrades the parent material properties, and the equipment is expensive and energy-intensive.

[0003] In recent years, electric field-assisted quick connection technology has attracted the attention of many researchers. By applying a DC electric field exceeding the threshold to the material, the connection can be completed in an extremely short time (seconds). Its application in the connection of yttrium oxide transparent ceramics and metals has profound significance for the development and application of yttrium oxide transparent ceramics. However, due to the mismatch in the thermal expansion coefficients of metals and ceramics, the residual stress of electric field-assisted direct connection is too large, which seriously reduces the quality and reliability of the joint. Therefore, it is necessary to design a method to alleviate the residual stress of electric field-assisted quick connection between yttrium oxide transparent ceramics and metals, and effectively control the impact of residual stress on the performance of the connector. Summary of the Invention

[0004] To address these issues, the present invention provides an interlayer connection material and method for alleviating residual stress in electric-field-assisted rapid connections between yttria transparent ceramic and metal. This approach aims to design and control the interlayer to achieve a transitional reaction interface, reducing residual stress in the joint region and significantly improving connection performance.

[0005] On the one hand, the present invention provides an intermediate layer connection material for alleviating the residual stress of yttrium oxide transparent ceramic and metal electric field assisted quick connection, wherein the intermediate layer connection material includes a hard metal intermediate layer, a soft metal intermediate layer or a composite intermediate layer starting from the yttrium oxide transparent ceramic side; the hard metal intermediate layer is selected from Ti and Cr, the soft metal intermediate layer is selected from Ni and Al, and the composite intermediate layer is selected from Ti / Ni, Ti / Al, Cr / Ni or Cr / Al.

[0006] The interlayer material provided by the present invention, which can alleviate residual stress in the connection between yttrium oxide transparent ceramic and metal, includes a specific hard metal interlayer, a soft metal interlayer, or a composite interlayer. In the composite interlayer, the hard metal interlayers of Ti and Cr are positioned closer to the yttrium oxide transparent ceramic, while the soft metal interlayers of Ni and Al are positioned closer to the metal to be connected. This achieves a gradient transition in thermal expansion coefficients, effectively alleviating residual stress.

[0007] The intermediate layer used in the present invention includes a hard metal intermediate layer, a soft metal intermediate layer or a composite intermediate layer. Compared with the electric field assisted direct connection without adding an intermediate layer, the present invention can effectively alleviate the residual stress generated during the connection process, improve the connection strength and quality, and the required connection time is significantly shortened, and the required current density is also significantly reduced. The method provided by the present invention for alleviating the residual stress of yttrium oxide transparent ceramic and metal electric field assisted rapid connection obtains a joint shear strength of ≥40MPa, and the mechanical properties of the connector are significantly improved. This is because the intermediate layer added by the present invention contains active elements, which can make the diffusion reaction process faster. At the same time, under the electromigration effect of the applied current, the diffusion rate of metal atoms is further accelerated. Therefore, the combined effect of the two further shortens the time required for connection.

[0008] The thickness of the hard metal intermediate layer is 400-800nm, the thickness of the soft metal intermediate layer is 400-800nm; the thickness of the composite intermediate layer is 600-800nm. Preferably, the thickness of the hard metal intermediate layer in the composite intermediate layer is 300-400nm, and the thickness of the soft metal intermediate layer is 300-400nm. If the intermediate layer is too thin, the reaction is insufficient, and almost all of the soft metal in the intermediate layer reacts with the parent material, thus having little effect on relieving residual stress. If the intermediate layer is too thick, it will lead to excessive reaction, and excessive products will increase the brittleness of the joint, which is not conducive to improving the connection strength.

[0009] The room temperature flexural strength of the yttrium oxide transparent ceramic to be connected is ≥150 MPa, the elastic modulus is ≥160 GPa, and the optical transmittance at a wavelength of 1050 nm is not less than 80%.

[0010] The metal to be joined comprises one of a titanium-based alloy, an iron-based alloy or a monel alloy. Preferably, the metal to be joined comprises titanium alloy TC4 (Ti-6Al-4V), Kovar alloy 4J29, iron-cobalt-nickel alloy 4J33, or monel alloy Monel400 (Ni68Cu28Fe).

[0011] On the other hand, the present invention also provides a method for alleviating residual stress in electric field assisted rapid connection of yttrium oxide transparent ceramic and metal by using the above-mentioned intermediate layer connection material, comprising: (1) preparing an intermediate layer on the surface to be connected of the yttrium oxide transparent ceramic that has been pre-treated by grinding, polishing and ultrasonic cleaning by a magnetron sputtering method; (2) assembling a sample to be connected in the order of first electrode / yttrium oxide transparent ceramic / intermediate layer / metal / second electrode and placing the sample in an electric field assisted diffusion connection device, applying an axial pressure of 0.1 to 1 MPa to the sample to be connected, and -3 Pa, heat it to 875-925℃ and apply an electric field to the sample to be connected through the electrode. When the current density reaches 1-5 mA / mm 2 Then, the power is continued to be supplied and the temperature is kept at 30 to 180 seconds, and finally the mixture is cooled to room temperature at a cooling rate of 3 to 5°C / min to obtain a yttrium oxide transparent ceramic / intermediate layer / metal connector.

[0012] The advantages of using magnetron sputtering to prepare the intermediate layer in the present invention are mainly two: first, the diversity of material selection. Magnetron sputtering does not require the target material to be resistant to high temperature and heat radiation, while the thermal spraying method has certain limitations in the selection of intermediate layer materials; second, compared with the thermal spraying method, the intermediate layer prepared by magnetron sputtering is of better quality, has high bonding strength and has no obvious defects.

[0013] In a preferred embodiment, the surfaces of the yttrium oxide transparent ceramic and the metal to be joined are ground and polished and ultrasonically cleaned in an ethanol solution to ensure that the surface roughness Ra of the yttrium oxide transparent ceramic to be joined is ≤ 0.1 μm and the surface roughness Ra of the metal to be joined is ≤ 5 μm.

[0014] Preferably, in step (1), the magnetron sputtering method comprises: placing the pretreated yttrium oxide transparent ceramic into the magnetron sputtering sample chamber, evacuating to 0.05-0.1 Pa, and radio-frequency cleaning the surface of the yttrium oxide transparent ceramic to be sputtered for 2-5 minutes at a power of 75-85 W; then evacuating the sputtering chamber to 5×10 -3 ~8×10 -3 Pa and heat to 175-225 ° C, pre-sputter at a power of 200-250 W for 5-10 minutes, then open the target baffle and base rotation switch, and perform magnetron sputtering at a sputtering power of 200-250 W.

[0015] Preferably, in step (1), the intermediate layer includes a hard metal intermediate layer, a soft metal intermediate layer or a composite intermediate layer; wherein the sputtering time of the hard metal intermediate layer is 20 to 40 minutes, the sputtering time of the soft metal intermediate layer is 20 to 40 minutes, the sputtering time of the hard metal intermediate layer in the composite intermediate layer is 15 to 20 minutes, and the sputtering time of the soft metal intermediate layer is 15 to 20 minutes.

[0016] Preferably, in step (1), the hard metal intermediate layer is Ti or Cr, the soft metal intermediate layer is Ni or Al, and the composite intermediate layer includes one of Ti / Ni, Ti / Al, Cr / Ni, and Cr / Al.

[0017] Preferably, in step (1), the thickness of the hard metal intermediate layer is 400-800 nm, and the thickness of the soft metal intermediate layer is 400-800 nm; when sputtering the composite intermediate layer, the thickness of the hard metal intermediate layer is 300-400 nm, and the thickness of the soft metal intermediate layer is 300-400 nm.

[0018] Preferably, in step (2), the direction of the applied electric field is from the first electrode to the second electrode, that is, from the yttrium oxide transparent ceramic side to the intermediate layer and finally to the metal side.

[0019] The present invention utilizes a mechanism for alleviating residual stress in the electric field-assisted quick connection of yttria transparent ceramic and metal: a soft metal interlayer utilizes the plastic deformation capability of the soft metal to alleviate residual stress in the joint; a hard metal interlayer, due to its low thermal expansion coefficient, close to that of the ceramic base material, can also alleviate residual stress; and a composite interlayer utilizes a thermal expansion coefficient gradient to alleviate residual stress. Conventional interlayers, such as metal foil, are too thick for this method. The present invention utilizes magnetron sputtering to produce the interlayer, enabling precise thickness adjustment at the nanometer level, more effectively alleviating residual stress and achieving superior bonding strength.

[0020] The reason for applying a DC electric field in this invention is that the DC threshold electric field applied is intended to stimulate the formation of a large number of oxygen defects within the ceramic, thereby achieving a connection within seconds. The mechanism of electric field-assisted bonding of ceramics and metals under an AC electric field is fundamentally different from that of the DC field used in this invention. The greatest advantage of applying a DC electric field in this invention is that it can shorten the bonding time from hours to seconds, thereby avoiding the damage to the parent metal caused by excessively high temperature bonding time.

[0021] The main reactions for oxygen vacancy generation are as follows: It can be seen that the gas concentration gradient under the vacuum environment of the present invention is more conducive to the release of oxygen, that is, it is more conducive to the reaction and the generation of oxygen defects. Compared with the AC electric field, the action mechanism of the DC electric field is significantly different. The AC electric field assisted diffusion connection mainly utilizes the thermal effect of the Joule action of the current, but it still takes a long time (h); the threshold electric field used in the present invention mainly stimulates the generation of a large number of oxygen defects inside the ceramic by applying a DC threshold electric field, which can achieve connection in seconds, avoiding damage to the base material itself due to long-term connection, and the Joule heating effect of the current is only a secondary effect.

[0022] The type of intermediate layer, thickness of the intermediate layer, current density, connection time, connection temperature, etc. of the present invention all play a decisive role in the rapid connection of yttrium oxide transparent ceramics and metals. The type of intermediate layer is directly linked to the actual effect of reaction products and relief of residual stress. The thickness of the intermediate layer affects the degree of reaction. If the intermediate layer is too thin, the reaction is insufficient, and almost all of the soft metal in the intermediate layer reacts with the base material, which has little effect on relieving residual stress. A thicker intermediate layer will lead to excessive reaction, and excessive products will increase the brittleness of the joint, which is not conducive to improving the connection strength. If the current density is too large, the excessive brittle phase generated at the connection interface will affect the connection strength; if the current density is too small, the reaction is insufficient and effective bonding cannot be achieved. If the connection time is too long, the interface reaction is excessive and the connection strength is damaged; if the connection time is too short, the reaction is incomplete and the connection cannot be achieved. If the connection temperature is too low, the reaction cannot be fully carried out. If the connection temperature is too high, the reaction is too intense and the strength is affected.

[0023] Beneficial effects

[0024] The method of alleviating residual stress in electric field-assisted quick connection of yttrium oxide transparent ceramic and metal of the present invention has the following advantages:

[0025] (1) Compared with electric field assisted direct connection without adding an intermediate layer, the present invention quickly realizes indirect connection between transparent ceramic and metal under the combined action of electric field and current by designing the intermediate layer material, which can effectively alleviate the residual stress generated during the connection process and improve the connection strength and quality.

[0026] (2) Compared with electric field assisted direct connection without adding an intermediate layer, the electric field assisted connection process is easier to carry out after adding a metal intermediate layer, the required connection time is significantly shortened, and the required current density is also significantly reduced, which gives it a greater advantage in production efficiency.

[0027] (3) The present invention can improve the effect of relieving residual stress by adjusting parameters such as the thickness of the intermediate layer, current density, and connection time. If the intermediate layer is too thin, the reaction is insufficient, and almost all of the soft metal in the intermediate layer reacts with the base material, which has little effect on relieving residual stress; if the intermediate layer is too thick, the generation of excessive brittle phases in the connection interface will affect the joint strength. If the current density is too large, the reaction will be excessive, resulting in excessive brittle phases, which is not conducive to relieving residual stress; if the current density is too small, the reaction is insufficient and effective bonding cannot be achieved. If the connection time is too long, the intermediate layer material reacts excessively with the base material, which is not conducive to relieving residual stress; if the connection time is too short, the reaction is incomplete and effective connection cannot be achieved. Different process parameters are coupled and affect each other, so it is necessary to adjust the process parameters according to the specific type and thickness of the intermediate layer to effectively improve the residual stress relief effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1Schematic diagram of the electric field assisted diffusion bonding device used in Example 1; Figure 2 This is a scanning electron microscope image of the interface between the yttrium oxide transparent ceramic / Ni / TC4 titanium alloy in Example 1; Figure 3 This is the X-ray diffraction pattern at the connection interface of the yttrium oxide transparent ceramic / Ni / TC4 titanium alloy connector of Example 1. DETAILED DESCRIPTION

[0029] To further illustrate the content, features and practical effects of the present invention, the present invention is described in detail below in conjunction with the embodiments. It should be noted that the modification method of the design of the present invention is not limited to these specific embodiments. Without departing from the spirit and connotation of the design of the present invention, equivalent replacements and modifications made by those skilled in the art based on the content of the present invention are also within the scope of the present invention.

[0030] The following is an exemplary description of a method for alleviating residual stress in electric field-assisted rapid connection between yttria transparent ceramic and metal using the intermediate layer connection material provided by the present invention.

[0031] An intermediate layer is prepared by magnetron sputtering on the surface to be connected of the yttrium oxide transparent ceramic that has been pretreated by grinding, polishing and ultrasonic cleaning.

[0032] In an optional embodiment, the surfaces of the yttrium oxide transparent ceramic and metal to be joined are ground and polished, and then ultrasonically cleaned in an ethanol solution to achieve a surface roughness Ra ≤ 0.1 μm for the yttrium oxide transparent ceramic surface and a surface roughness Ra ≤ 5 μm for the metal surface. Excessive roughness on the ceramic side can affect the quality of the intermediate layer prepared by magnetron sputtering. However, the roughness requirement on the metal side, which contacts the intermediate layer, can be appropriately reduced.

[0033] The magnetron sputtering method comprises: placing the pretreated yttrium oxide transparent ceramic into a magnetron sputtering sample chamber, evacuating the chamber to a vacuum of 0.05 to 0.1 Pa, and performing radio frequency cleaning on the surface of the yttrium oxide transparent ceramic to be sputtered for 2 to 5 minutes at a power of 75 to 85 W; then evacuating the sputtering chamber to a vacuum of 5×10 -3 ~8×10 -3 Pa and heat to 175-225 ° C, pre-sputter at a power of 200-250 W for 5-10 minutes, then open the target baffle and base rotation switch, and perform magnetron sputtering at a sputtering power of 200-250 W.

[0034] The intermediate layer includes a hard metal intermediate layer, a soft metal intermediate layer, or a composite intermediate layer. The sputtering time for the hard metal intermediate layer is 20 to 40 minutes, the sputtering time for the soft metal intermediate layer is 20 to 40 minutes, and the sputtering time for the hard metal intermediate layer in the composite intermediate layer is 15 to 20 minutes, and the sputtering time for the soft metal intermediate layer is 15 to 20 minutes. Sputtering the intermediate layer for too long will result in an excessively thick intermediate layer, which is not conducive to relieving residual stress and will prevent effective connection.

[0035] The hard metal intermediate layer is made of Ti or Cr, because its thermal expansion coefficient is close to that of ceramic materials, which can alleviate the residual stress of the joint to a certain extent; the soft metal intermediate layer is made of Ni or Al, and the plastic deformation and creep deformation of the soft metal are used to alleviate the residual stress of the joint; the composite intermediate layer is made of one of Ti / Ni, Ti / Al, Cr / Ni, and Cr / Al to achieve a gradient transition of the thermal expansion coefficient of the connection interface, thereby alleviating the residual stress of the joint. As mentioned above, the present invention uses a threshold electric field to excite a large number of oxygen defects to achieve ultra-fast connection within seconds, the main function of which is to reduce the time required for connection to avoid damage to the parent material. In order to further improve the connection strength, the present invention chooses to add soft metal layers, hard metal layers, and composite metal layers. The soft metal intermediate layer is selected to utilize the plastic deformation ability of the soft metal to alleviate the residual stress of the joint; the hard metal intermediate layer is selected because its thermal expansion coefficient is low and close to that of the ceramic parent material, which can alleviate the residual stress; the composite intermediate layer is selected to alleviate the residual stress through a gradient transition of the thermal expansion coefficient. Specific experiments have found that the addition of these intermediate layer metals has a promoting effect on diffusion and reaction, further shortening the connection time and the required current density.

[0036] The thickness of the hard metal intermediate layer is controlled to be 400-800nm; the thickness of the soft metal intermediate layer is controlled to be 400-800nm. When the composite intermediate layer is sputtered, the total thickness of the composite intermediate layer is controlled to be 600-800nm, of which the thickness of the hard metal intermediate layer is controlled to be 300-400nm, and the thickness of the soft metal intermediate layer is controlled to be 300-400nm. If the intermediate layer is too thin, the residual stress cannot be effectively relieved; if the intermediate layer is too thick, the formation of excessive brittle phases in the joint interface will affect the joint strength.

[0037] The sample to be connected is assembled in the order of first electrode / yttrium oxide transparent ceramic / intermediate layer / metal / second electrode and placed in the electric field assisted diffusion bonding device. An axial pressure of 0.1 to 1 MPa is applied to the sample to be connected. The sample is placed in a vacuum of ≤6×10 -3 Pa, heat it to 875-925℃ and apply an electric field to the sample to be connected through the electrode. When the current density reaches 1-5 mA / mm 2Then, the power is continued to be supplied and the temperature is kept at 30 to 180 seconds, and finally the mixture is cooled to room temperature at a cooling rate of 3 to 5°C / min to obtain a yttrium oxide transparent ceramic / intermediate layer / metal connector.

[0038] In an optional embodiment, the direction of the applied electric field is from the first electrode to the second electrode, that is, from the yttrium oxide transparent ceramic side to the intermediate layer and finally to the metal side.

[0039] The axial pressure is preferably 0.5 MPa. If it is too small, effective connection cannot be achieved. If the vacuum degree in the furnace chamber is too large, it is not conducive to creating an environment that promotes the generation of oxygen defects.

[0040] The heating temperature is preferably 900° C. A lower heating temperature will result in insufficient reaction, while a higher heating temperature will result in excessive reaction and excessive residual stress.

[0041] The cooling rate is preferably 3°C / min. A lower cooling rate will result in a lengthy connection process and affect efficiency, while a higher cooling rate will result in excessive residual stress.

[0042] The purpose of the electric field-assisted quick connection of the present invention in a vacuum environment is to promote the generation of oxygen defects and prevent metal oxidation. Compared with the non-vacuum environment in the prior art, the advantages of the vacuum environment of the present invention are: the gas concentration gradient in the vacuum environment is more conducive to the release of oxygen, that is, it is more conducive to the reaction and the generation of oxygen defects, and can effectively avoid the oxidation of the metal base material.

[0043] The current density can be controlled to be 1-5 mA / mm 2 If the current density is too high, the excessive brittle phase generated at the bonding interface will affect the bonding strength. If the current density is too low, the reaction will be insufficient and no effective bonding will be achieved. The time for maintaining a constant current density, i.e., the bonding time, can be 30 to 180 seconds. If the bonding time is too long, excessive interfacial reaction will impair the bonding strength. If the bonding time is too short, the reaction will be incomplete and no bonding will be achieved.

[0044] This invention uses a method for alleviating residual stress in electric-field-assisted rapid bonding of yttrium oxide transparent ceramics and metals. By adding a hard metal interlayer, a soft metal interlayer, or a composite interlayer, this method effectively alleviates residual stress at the bonding interface. Compared to direct electric-field-assisted bonding of yttrium oxide transparent ceramics and metals, the addition of an interlayer significantly improves joint quality and reliability while further shortening bonding time.

[0045] The following examples are further given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention all fall within the scope of protection of the present invention. The specific process parameters and the like in the following examples are only examples within a suitable range, that is, those skilled in the art can make selections within a suitable range through the description herein, and are not limited to the specific numerical values ​​exemplified below.

[0046] Example 1

[0047] In Example 1, Ni is used as a soft metal intermediate layer to electrically connect a yttrium oxide transparent ceramic and a TC4 titanium alloy. The yttrium oxide transparent ceramic base material has a room temperature flexural strength of ≥160 MPa, an elastic modulus of ≥150 GPa, and an optical transmittance of not less than 80% at a wavelength of 1050 nm. The specific connection method is as follows:

[0048] (1) Process the ceramic base material and the metal base material into 15×12×2mm 3 The surfaces to be joined are ground and polished, and impurities and oil are removed by ultrasonic treatment in an ethanol solution. The surface roughness of the yttrium oxide transparent ceramic surface to be joined is Ra ≤ 0.1 μm, and the surface roughness of the TC4 titanium alloy surface to be joined is Ra ≤ 5 μm.

[0049] (2) Place the ultrasonically cleaned yttrium oxide transparent ceramic into the magnetron sputtering sample chamber and evacuate the sample chamber to 10 - 1 Pa and RF clean the transparent ceramic surface to be sputtered for 3 minutes at 80W power. Then evacuate the sputtering chamber and carry out the sample delivery process. -3 Pa, the temperature was raised to 200 °C, and the Ni target was pre-sputtered at a power of 200 W for 10 min. Then the target baffle and base rotation switch were opened, and the Ni target was magnetron sputtered at a sputtering power of 230 W for 30 min.

[0050] (3) The yttrium oxide transparent ceramic after magnetron sputtering the intermediate layer is combined with the TC4 titanium alloy in the order of electrode / ceramic / intermediate layer / metal / electrode (e.g. Figure 1 As shown in Figure 2), it is assembled in the electric field assisted diffusion bonding device. Apply 0.5 MPa axial pressure to the assembly and wait until the vacuum degree in the furnace chamber reaches 6×10 -3 After heating to 900°C at 1000 Pa, an electric field is applied from the first electrode to the second electrode. When the current density reaches 1 mA / mm 2 The mixture was then maintained for 60 seconds and cooled to room temperature at a cooling rate of 3°C / min to obtain a yttria transparent ceramic / Ni / TC4 titanium alloy connector.

[0051] Detected by a universal testing machine CLY30, the shear strength of the connector prepared in Example 2 was 69 MPa, and the thickness of the Ni intermediate layer was 550 nm.

[0052] Figure 2 This is a scanning electron microscope image of the interface between the yttria transparent ceramic / Ni / TC4 titanium alloy joint in Example 1. The image demonstrates effective bonding, with no apparent defects at the interface and a good bond. The Ni in the intermediate layer reacts with the base material through diffusion, with the reactants distributed at the α-phase grain boundaries within the TC4.

[0053] Figure 3 This is the X-ray diffraction diagram of the connection interface of the yttrium oxide transparent ceramic / Ni / TC4 titanium alloy connector of Example 1. It can be seen from the figure that relevant reactants are generated at the interface after connection.

[0054] Example 2

[0055] In Example 2, Ni is used as a soft metal intermediate layer to electrically connect yttrium oxide transparent ceramic and Monel 400 alloy using an electric field-assisted method. The yttrium oxide transparent ceramic base material has a room temperature flexural strength of ≥160 MPa, an elastic modulus of ≥150 GPa, and an optical transmittance of not less than 80% at a wavelength of 1050 nm. The specific connection method is as follows:

[0056] (1) Process the ceramic base material and the metal base material into 15×12×2mm 3 The surfaces to be joined are ground and polished, and impurities and oil are removed by ultrasonic treatment in an ethanol solution. The surface roughness of the yttrium oxide transparent ceramic surface to be joined is Ra ≤ 0.1 μm, and the surface roughness of the Monel 400 alloy surface to be joined is Ra ≤ 5 μm.

[0057] (2) Place the ultrasonically cleaned yttrium oxide transparent ceramic into the magnetron sputtering sample chamber and evacuate the sample chamber to 10 - 1 Pa and RF clean the transparent ceramic surface to be sputtered for 3 minutes at 80W power. Then evacuate the sputtering chamber and carry out the sample delivery process. -3 Pa, the temperature was raised to 200 °C, and the Ni target was pre-sputtered at a power of 200 W for 10 min. Then the target baffle and base rotation switch were opened, and the Ni target was magnetron sputtered at a sputtering power of 210 W for 25 min.

[0058] (3) The yttrium oxide transparent ceramic after magnetron sputtering the intermediate layer and Monel400 alloy are assembled in the order of electrode / ceramic / intermediate layer / metal / electrode and assembled in the electric field assisted diffusion bonding device. An axial pressure of 0.5 MPa is applied to the assembly until the vacuum degree in the furnace chamber reaches 4×10-3 After heating to 900°C at 1.5 Pa, an electric field is applied from the first electrode to the second electrode. When the current density reaches 3 mA / mm 2 The temperature was then maintained for 120 s and cooled to room temperature at a cooling rate of 3°C / min to obtain a yttrium oxide transparent ceramic / Ni / Monel400 alloy connector.

[0059] Detected by a universal testing machine CLY30, the shear strength of the connector prepared in Example 5 was 62 MPa, and the thickness of the Ni intermediate layer was 460 nm.

[0060] Example 3

[0061] In Example 3, Al is used as a soft metal intermediate layer to electrically connect a yttrium oxide transparent ceramic and a TC4 titanium alloy. The yttrium oxide transparent ceramic base material has a room temperature flexural strength of ≥160 MPa, an elastic modulus of ≥150 GPa, and an optical transmittance of ≥80% at a wavelength of 1050 nm. The specific connection method is as follows:

[0062] (1) Process the ceramic base material and the metal base material into 15×12×2mm 3 The surfaces to be joined are ground and polished, and impurities and oil are removed by ultrasonic treatment in an ethanol solution. The surface roughness of the yttrium oxide transparent ceramic surface to be joined is Ra ≤ 0.1 μm, and the surface roughness of the TC4 titanium alloy surface to be joined is Ra ≤ 5 μm.

[0063] (2) Place the ultrasonically cleaned yttrium oxide transparent ceramic into the magnetron sputtering sample chamber and evacuate the sample chamber to 10 - 1 Pa and RF clean the transparent ceramic surface to be sputtered for 3 minutes at 80W power. Then evacuate the sputtering chamber and carry out the sample delivery process. -3 Pa, the temperature was raised to 200 °C, and the Al target was pre-sputtered at a power of 200 W for 10 min. Then the target baffle and base rotation switch were opened, and the Al target was magnetron sputtered at a sputtering power of 225 W for 20 min.

[0064] (3) The yttrium oxide transparent ceramic after magnetron sputtering the intermediate layer and the TC4 titanium alloy are assembled in the order of electrode / ceramic / intermediate layer / metal / electrode and assembled in the electric field assisted diffusion bonding device. An axial pressure of 0.5 MPa is applied to the assembly until the vacuum degree in the furnace chamber reaches 6×10 -3 After heating to 900°C at 1.5 Pa, an electric field is applied from the first electrode to the second electrode. When the current density reaches 4 mA / mm 2 The mixture was then maintained for 120 s and cooled to room temperature at a cooling rate of 3°C / min to obtain a yttrium oxide transparent ceramic / Al / TC4 titanium alloy connector.

[0065] Detected by a universal testing machine CLY30, the shear strength of the connector prepared in Example 3 was 53 MPa, and the thickness of the Al intermediate layer was 360 nm.

[0066] Example 4

[0067] In Example 4, Al is used as a soft metal intermediate layer to electrically connect a yttrium oxide transparent ceramic and a TC4 titanium alloy. The yttrium oxide transparent ceramic base material has a room temperature flexural strength of ≥160 MPa, an elastic modulus of ≥150 GPa, and an optical transmittance of ≥80% at a wavelength of 1050 nm. The specific connection method is as follows:

[0068] (1) Process the ceramic base material and the metal base material into 15×12×2mm 3 The surfaces to be joined are ground and polished, and impurities and oil are removed by ultrasonic treatment in an ethanol solution. The surface roughness of the yttrium oxide transparent ceramic surface to be joined is Ra ≤ 0.1 μm, and the surface roughness of the TC4 titanium alloy surface to be joined is Ra ≤ 5 μm.

[0069] (2) Place the ultrasonically cleaned yttrium oxide transparent ceramic into the magnetron sputtering sample chamber and evacuate the sample chamber to 10 - 1 Pa and RF clean the transparent ceramic surface to be sputtered for 3 minutes at 80W power. Then evacuate the sputtering chamber and carry out the sample delivery process. -3 Pa, the temperature was raised to 200 °C, and the Al target was pre-sputtered at a power of 200 W for 10 min. Then the target baffle and base rotation switch were opened, and the Al target was magnetron sputtered at a sputtering power of 210 W for 30 min.

[0070] (3) The yttrium oxide transparent ceramic after magnetron sputtering the intermediate layer and the TC4 titanium alloy are assembled in the order of electrode / ceramic / intermediate layer / metal / electrode and assembled in the electric field assisted diffusion bonding device. An axial pressure of 0.5 MPa is applied to the assembly until the vacuum degree in the furnace chamber reaches 5×10 -3 After heating to 900°C at 1.5 Pa, an electric field is applied from the first electrode to the second electrode. When the current density reaches 3.5 mA / mm 2 The mixture was then maintained for 30 seconds and cooled to room temperature at a cooling rate of 3°C / min to obtain a yttria transparent ceramic / Al / TC4 titanium alloy connector.

[0071] Detected by a universal testing machine CLY30, the shear strength of the connector prepared in Example 4 was 48 MPa, and the thickness of the Al intermediate layer was 550 nm.

[0072] Example 5

[0073] In Example 5, Ti is used as a hard metal intermediate layer to achieve electric field-assisted bonding of yttrium oxide transparent ceramic and TC4 titanium alloy. The yttrium oxide transparent ceramic base material has a room temperature flexural strength of ≥160 MPa, an elastic modulus of ≥150 GPa, and an optical transmittance of ≥80% at a wavelength of 1050 nm. The specific bonding method is as follows:

[0074] (1) Process the ceramic base material and the metal base material into 15×12×2mm 3 The surfaces to be joined are ground and polished, and impurities and oil are removed by ultrasonic treatment in an ethanol solution. The surface roughness of the yttrium oxide transparent ceramic surface to be joined is Ra ≤ 0.1 μm, and the surface roughness of the TC4 titanium alloy surface to be joined is Ra ≤ 5 μm.

[0075] (2) Place the ultrasonically cleaned yttrium oxide transparent ceramic into the magnetron sputtering sample chamber and evacuate the sample chamber to 10 - 1 Pa and RF clean the transparent ceramic surface to be sputtered for 3 minutes at 80W power. Then evacuate the sputtering chamber and carry out the sample delivery process. -3 Pa, the temperature was raised to 200 °C, and the Ti target was pre-sputtered at a power of 200 W for 10 min. After that, the target baffle and the base rotation switch were opened, and the Ti target was magnetron sputtered at a sputtering power of 200 W for 30 min.

[0076] (3) The yttrium oxide transparent ceramic after magnetron sputtering the intermediate layer and the TC4 titanium alloy are assembled in the order of electrode / ceramic / intermediate layer / metal / electrode and assembled in the electric field assisted diffusion bonding device. An axial pressure of 0.5 MPa is applied to the assembly until the vacuum degree in the furnace chamber reaches 6×10 -3 After heating to 900°C at 1000 Pa, an electric field is applied from the first electrode to the second electrode. When the current density reaches 1 mA / mm 2 The temperature was then maintained for 180 seconds and cooled to room temperature at a cooling rate of 3°C / min to obtain a yttria transparent ceramic / Ti / TC4 titanium alloy connector.

[0077] According to the test of the universal testing machine CLY30, the shear strength of the connector prepared in Example 5 is 50 MPa, and the thickness of the Ti intermediate layer is 450 nm.

[0078] Example 6

[0079] In Example 6, Ti is used as a hard metal intermediate layer to achieve electric field-assisted bonding of a yttrium oxide transparent ceramic and a 4J29 alloy. The yttrium oxide transparent ceramic base material has a room temperature flexural strength of ≥160 MPa, an elastic modulus of ≥150 GPa, and an optical transmittance of ≥80% at a wavelength of 1050 nm. The specific bonding method is as follows:

[0080] (1) Process the ceramic base material and the metal base material into 15×12×2mm 3 The surfaces to be joined are ground and polished, and impurities and oil are removed by ultrasonic treatment in an ethanol solution. The surface roughness of the yttrium oxide transparent ceramic surface to be joined is Ra ≤ 0.1 μm, and the surface roughness of the 4J29 alloy surface to be joined is Ra ≤ 5 μm.

[0081] (2) Place the ultrasonically cleaned yttrium oxide transparent ceramic into the magnetron sputtering sample chamber and evacuate the sample chamber to 10 - 1 Pa and RF clean the transparent ceramic surface to be sputtered for 3 minutes at 80W power. Then evacuate the sputtering chamber and carry out the sample delivery process. -3 Pa, the temperature was raised to 200 °C, and the Ti target was pre-sputtered at a power of 200 W for 10 min. Then the target baffle and the base rotation switch were opened, and magnetron sputtering was performed using the Ti target at a sputtering power of 250 W for 20 min.

[0082] (3) The yttrium oxide transparent ceramic after magnetron sputtering the intermediate layer and the 4J29 alloy are assembled in the order of electrode / ceramic / intermediate layer / metal / electrode and assembled in the electric field assisted diffusion bonding device. An axial pressure of 0.5 MPa is applied to the assembly until the vacuum degree in the furnace chamber reaches 5×10 -3 After heating to 900°C at 1.5 Pa, an electric field is applied from the first electrode to the second electrode. When the current density reaches 5 mA / mm 2 The mixture was then maintained at this temperature for 30 seconds and cooled to room temperature at a cooling rate of 3°C / min to obtain a yttria transparent ceramic / Ti / 4J29 alloy connector.

[0083] Detected by a universal testing machine CLY30, the shear strength of the connector prepared in Example 6 was 45 MPa, and the thickness of the Ti intermediate layer was 325 nm.

[0084] Example 7

[0085] In Example 7, Cr is used as a hard metal intermediate layer to electrically connect a yttrium oxide transparent ceramic and a TC4 titanium alloy. The yttrium oxide transparent ceramic base material has a room temperature flexural strength of ≥160 MPa, an elastic modulus of ≥150 GPa, and an optical transmittance of ≥80% at a wavelength of 1050 nm. The specific connection method is as follows:

[0086] (1) Process the ceramic base material and the metal base material into 15×12×2mm 3The surfaces to be joined are ground and polished, and impurities and oil are removed by ultrasonic treatment in an ethanol solution. The surface roughness of the yttrium oxide transparent ceramic surface to be joined is Ra ≤ 0.1 μm, and the surface roughness of the TC4 titanium alloy surface to be joined is Ra ≤ 5 μm.

[0087] (2) Place the ultrasonically cleaned yttrium oxide transparent ceramic into the magnetron sputtering sample chamber and evacuate the sample chamber to 10 - 1 Pa and RF clean the transparent ceramic surface to be sputtered for 3 minutes at 80W power. Then evacuate the sputtering chamber and carry out the sample delivery process. -3 Pa, and pre-sputtered the Cr target for 10 min at a power of 200 W. Then, the target baffle and the base rotation switch were turned on, and magnetron sputtering was performed using the Cr target at a sputtering power of 220 W for 40 min.

[0088] (3) The yttrium oxide transparent ceramic after magnetron sputtering the intermediate layer and the TC4 titanium alloy are assembled in the order of electrode / ceramic / intermediate layer / metal / electrode and assembled in the electric field assisted diffusion bonding device. An axial pressure of 0.5 MPa is applied to the assembly until the vacuum degree in the furnace chamber reaches 3×10 -3 After heating to 900°C at 1.5 Pa, an electric field is applied from the first electrode to the second electrode. When the current density reaches 2 mA / mm 2 The temperature was then maintained for 120 s and cooled to room temperature at a cooling rate of 3°C / min to obtain a yttria transparent ceramic / Cr / TC4 titanium alloy connector.

[0089] Detected by a universal testing machine CLY30, the shear strength of the connector prepared in Example 7 was 43 MPa, and the thickness of the Cr intermediate layer was 580 nm.

[0090] Example 8

[0091] In Example 8, Cr is used as a hard metal intermediate layer to electrically connect a yttrium oxide transparent ceramic and a 4J33 alloy. The yttrium oxide transparent ceramic base material has a room temperature flexural strength of ≥160 MPa, an elastic modulus of ≥150 GPa, and an optical transmittance of ≥80% at a wavelength of 1050 nm. The specific connection method is as follows:

[0092] (1) Process the ceramic base material and the metal base material into 15×12×2mm 3 The surfaces to be joined are ground and polished, and impurities and oil are removed by ultrasonic treatment in an ethanol solution. The surface roughness of the yttrium oxide transparent ceramic surface to be joined is Ra ≤ 0.1 μm, and the surface roughness of the 4J33 alloy surface to be joined is Ra ≤ 5 μm.

[0093] (2) Place the ultrasonically cleaned yttrium oxide transparent ceramic into the magnetron sputtering sample chamber and evacuate the sample chamber to 10 - 1 Pa and RF clean the transparent ceramic surface to be sputtered for 3 minutes at 80W power. Then evacuate the sputtering chamber and carry out the sample delivery process. -3 Pa, the temperature was raised to 200 ° C, and the Cr target was pre-sputtered at a power of 200 W for 10 minutes. After that, the target baffle and the base rotation switch were opened, and the Cr target was magnetron sputtered at a sputtering power of 200 W for 30 minutes.

[0094] (3) The yttrium oxide transparent ceramic after magnetron sputtering the intermediate layer and the 4J33 alloy are assembled in the order of electrode / ceramic / intermediate layer / metal / electrode and assembled in the electric field assisted diffusion bonding device. An axial pressure of 0.5 MPa is applied to the assembly until the vacuum degree in the furnace chamber reaches 5×10 -3 After heating to 900°C at 1.5 Pa, an electric field is applied from the first electrode to the second electrode. When the current density reaches 2.5 mA / mm 2 The temperature was then maintained for 90 seconds and cooled to room temperature at a cooling rate of 3°C / min to obtain a yttria transparent ceramic / Cr / 4J33 alloy connector.

[0095] Detected by a universal testing machine CLY30, the shear strength of the connector prepared in Example 8 was 45 MPa, and the thickness of the Cr intermediate layer was 440 nm.

[0096] Example 9

[0097] In Example 9, a Ti / Ni composite interlayer is used to electrically connect a yttrium oxide transparent ceramic to a TC4 titanium alloy. The yttrium oxide transparent ceramic base material has a room temperature flexural strength of ≥160 MPa, an elastic modulus of ≥150 GPa, and an optical transmittance of ≥80% at a wavelength of 1050 nm. The specific connection method is as follows:

[0098] (1) Process the ceramic base material and the metal base material into 15×12×2mm 3 The surfaces to be joined are ground and polished, and impurities and oil are removed by ultrasonic treatment in an ethanol solution. The surface roughness of the yttrium oxide transparent ceramic surface to be joined is Ra ≤ 0.1 μm, and the surface roughness of the TC4 titanium alloy surface to be joined is Ra ≤ 5 μm.

[0099] (2) Place the ultrasonically cleaned yttrium oxide transparent ceramic into the magnetron sputtering sample chamber and evacuate the sample chamber to 10 - 1Pa and RF clean the transparent ceramic surface to be sputtered for 3 minutes at 80W power. Then evacuate the sputtering chamber and carry out the sample delivery process. -3 Pa, and then the temperature was raised to 200 ° C. After pre-sputtering the Ti target for 10 minutes at a power of 200 W, the target baffle and the base rotation switch were turned on. The Ti target was used for magnetron sputtering at a sputtering power of 235 W for 15 minutes. Then, the Ni target was pre-sputtered for 10 minutes, and then the target baffle and the base rotation switch were turned on. The Ni target was used for magnetron sputtering at a sputtering power of 235 W for 15 minutes.

[0100] (3) The yttrium oxide transparent ceramic after magnetron sputtering the intermediate layer and the TC4 titanium alloy are assembled in the order of electrode / ceramic / intermediate layer / metal / electrode and assembled in the electric field assisted diffusion bonding device. An axial pressure of 0.5 MPa is applied to the assembly until the vacuum degree in the furnace chamber reaches 6×10 -3 After heating to 900°C at 1.5 Pa, an electric field is applied from the first electrode to the second electrode. When the current density reaches 1.5 mA / mm 2 The temperature was then maintained for 180 s and cooled to room temperature at a cooling rate of 3°C / min to obtain a yttria transparent ceramic / Ti / Ni / TC4 titanium alloy connector.

[0101] According to the test of the universal testing machine CLY30, the shear strength of the connector prepared in Example 9 is 78 MPa, and the thickness of the Ti / Ni intermediate layer is 500 nm.

[0102] Example 10

[0103] In Example 10, a Ti / Al composite interlayer is used to electrically connect a yttrium oxide transparent ceramic to a TC4 titanium alloy. The yttrium oxide transparent ceramic matrix has a room temperature flexural strength of ≥160 MPa, an elastic modulus of ≥150 GPa, and an optical transmittance of ≥80% at a wavelength of 1050 nm. The specific connection method is as follows:

[0104] (1) Process the ceramic base material and the metal base material into 15×12×2mm 3 The surfaces to be joined are ground and polished, and impurities and oil are removed by ultrasonic treatment in an ethanol solution. The surface roughness of the yttrium oxide transparent ceramic surface to be joined is Ra ≤ 0.1 μm, and the surface roughness of the TC4 titanium alloy surface to be joined is Ra ≤ 5 μm.

[0105] (2) Place the ultrasonically cleaned yttrium oxide transparent ceramic into the magnetron sputtering sample chamber and evacuate the sample chamber to 10 - 1Pa and RF clean the transparent ceramic surface to be sputtered for 3 minutes at 80W power. Then evacuate the sputtering chamber and carry out the sample delivery process. -3 Pa, and then the temperature was raised to 200 ° C. After pre-sputtering the Ti target for 10 minutes at a power of 200 W, the target baffle and the base rotation switch were opened. The Ti target was used for magnetron sputtering at a sputtering power of 220 W for 15 minutes. Then, the Al target was pre-sputtered for 10 minutes, and then the target baffle and the base rotation switch were opened. The Al target was used for magnetron sputtering at a sputtering power of 220 W for 20 minutes.

[0106] (3) The yttrium oxide transparent ceramic after magnetron sputtering the intermediate layer and the TC4 titanium alloy are assembled in the order of electrode / ceramic / intermediate layer / metal / electrode and assembled in the electric field assisted diffusion bonding device. An axial pressure of 0.5 MPa is applied to the assembly until the vacuum degree in the furnace chamber reaches 5×10 -3 After heating to 900°C at 1000 Pa, an electric field is applied from the first electrode to the second electrode. When the current density reaches 1 mA / mm 2 The mixture was then maintained for 120 s and cooled to room temperature at a cooling rate of 3°C / min to obtain a yttria transparent ceramic / Ti / Al / TC4 titanium alloy connector.

[0107] Detected by a universal testing machine CLY30, the shear strength of the connector prepared in Example 10 was 72 MPa, and the thickness of the Ti / Al intermediate layer was 580 nm.

[0108] Example 11

[0109] In Example 11, a Cr / Ni composite interlayer is used to electrically connect a yttrium oxide transparent ceramic to a TC4 titanium alloy. The yttrium oxide transparent ceramic base material has a room temperature flexural strength of ≥160 MPa, an elastic modulus of ≥150 GPa, and an optical transmittance of ≥80% at a wavelength of 1050 nm. The specific connection method is as follows:

[0110] (1) Process the ceramic base material and the metal base material into 15×12×2mm 3 The surfaces to be joined are ground and polished, and impurities and oil are removed by ultrasonic treatment in an ethanol solution. The surface roughness of the yttrium oxide transparent ceramic surface to be joined is Ra ≤ 0.1 μm, and the surface roughness of the TC4 titanium alloy surface to be joined is Ra ≤ 5 μm.

[0111] (2) Place the ultrasonically cleaned yttrium oxide transparent ceramic into the magnetron sputtering sample chamber and evacuate the sample chamber to 10 - 1Pa and RF clean the transparent ceramic surface to be sputtered for 3 minutes at 80W power. Then evacuate the sputtering chamber and carry out the sample delivery process. -3 Pa, and pre-sputter the Cr target for 10 minutes at a power of 200 W, then open the target baffle and the base rotation switch, and use the Cr target for magnetron sputtering at a sputtering power of 200 W for 20 minutes. Then, pre-sputter the Ni target for 10 minutes, then open the target baffle and the base rotation switch, and use the Ni target for magnetron sputtering at a sputtering power of 200 W for 20 minutes.

[0112] (3) The yttrium oxide transparent ceramic after magnetron sputtering the intermediate layer and the TC4 titanium alloy are assembled in the order of electrode / ceramic / intermediate layer / metal / electrode and assembled in the electric field assisted diffusion bonding device. An axial pressure of 0.5 MPa is applied to the assembly until the vacuum degree in the furnace chamber reaches 5×10 -3 After heating to 900°C at 1.5 Pa, an electric field is applied from the first electrode to the second electrode. When the current density reaches 4.5 mA / mm 2 The mixture was then maintained at this temperature for 30 seconds and cooled to room temperature at a cooling rate of 3°C / min to obtain a yttria transparent ceramic / Cr / Ni / TC4 titanium alloy connector.

[0113] According to the test of the universal testing machine CLY30, the shear strength of the connector prepared in Example 11 is 67 MPa, and the thickness of the Cr / Ni intermediate layer is 700 nm.

[0114] Example 12

[0115] In Example 12, a Cr / Al composite interlayer is used to electrically connect a yttrium oxide transparent ceramic to a TC4 titanium alloy. The yttrium oxide transparent ceramic base material has a room temperature flexural strength of ≥160 MPa, an elastic modulus of ≥150 GPa, and an optical transmittance of ≥80% at a wavelength of 1050 nm. The specific connection method is as follows:

[0116] (1) Process the ceramic base material and the metal base material into 15×12×2mm 3 The surfaces to be joined are ground and polished, and impurities and oil are removed by ultrasonic treatment in an ethanol solution. The surface roughness of the yttrium oxide transparent ceramic surface to be joined is Ra ≤ 0.1 μm, and the surface roughness of the TC4 titanium alloy surface to be joined is Ra ≤ 5 μm.

[0117] (2) Place the ultrasonically cleaned yttrium oxide transparent ceramic into the magnetron sputtering sample chamber and evacuate the sample chamber to 10 - 1Pa and RF clean the transparent ceramic surface to be sputtered for 3 minutes at 80W power. Then evacuate the sputtering chamber and carry out the sample delivery process. -3 Pa, and pre-sputter the Cr target for 10 minutes at a power of 200 W, then open the target baffle and the base rotation switch, and use the Cr target for magnetron sputtering at a sputtering power of 220 W for 20 minutes. Then, pre-sputter the Al target for 10 minutes, then open the target baffle and the base rotation switch, and use the Al target for magnetron sputtering at a sputtering power of 220 W for 15 minutes.

[0118] (3) The yttrium oxide transparent ceramic after magnetron sputtering the intermediate layer and the TC4 titanium alloy are assembled in the order of electrode / ceramic / intermediate layer / metal / electrode and assembled in the electric field assisted diffusion bonding device. An axial pressure of 0.5 MPa is applied to the assembly until the vacuum degree in the furnace chamber reaches 6×10 -3 After heating to 900°C at 1.5 Pa, an electric field is applied from the first electrode to the second electrode. When the current density reaches 2 mA / mm 2 The mixture was then maintained for 60 seconds and cooled to room temperature at a cooling rate of 3°C / min to obtain a yttria transparent ceramic / Cr / Al / TC4 titanium alloy connector.

[0119] Detected by a universal testing machine CLY30, the shear strength of the connector prepared in Example 12 was 70 MPa, and the thickness of the Cr / Al intermediate layer was 570 nm.

[0120] Comparative Example 1

[0121] The magnetron sputtering intermediate layer and electric field assisted rapid connection process in this comparative example 1 were similar to those in Example 5, except that the connection time of the electric field assisted rapid connection was extended to 300 seconds. The resulting yttrium oxide transparent ceramic / Ti / TC4 titanium alloy was not connected.

[0122] Comparative Example 2

[0123] The magnetron sputtering intermediate layer and the electric field assisted quick connection process in this comparative example 2 refer to Example 2, except that the current density of the electric field assisted quick connection is increased to 10 mA / mm 2 The obtained yttrium oxide transparent ceramic / Ni / Monel400 alloy was not connected.

[0124] Comparative Example 3

[0125] The magnetron sputtering interlayer and electric field-assisted rapid bonding process in Comparative Example 3 was similar to that in Example 4, except that the magnetron sputtering time was extended to 50 minutes, and the resulting Al soft metal interlayer thickness was 950 nm. The resulting yttrium oxide transparent ceramic / Al / TC4 titanium alloy bond was not achieved.

[0126] Comparative Example 4

[0127] The magnetron sputtering interlayer and electric field-assisted rapid bonding process in Comparative Example 4 was similar to that in Example 10, except that the magnetron sputtering time was extended to 25 or 35 minutes, and the resulting Ti / Al composite interlayer had a thickness of 1050 nm. However, the resulting yttrium oxide transparent ceramic / Ti / Al / TC4 titanium alloy was not bonded.

[0128] Table 1 lists the thickness of the intermediate layers and the shear strength of the connector joints prepared in Examples 1 to 12 and Comparative Examples 1 to 4.

[0129] Table 1:

[0130] It can be seen from Table 1 that the strength of the connector with the composite intermediate layer is generally higher than the strength of the connector with a simple intermediate layer, but the specific shear strength still needs to be combined with the process parameters used. The results of Example 4 and Comparative Example 3, and Example 10 and Comparative Example 4 show that too long a magnetron sputtering time causes the intermediate layer to be too thick, which is not conducive to the relief of residual stress and will result in an inability to achieve effective connection. The results of Example 5 and Comparative Example 1 show that the connection strength is affected by the connection time. If the connection time is too long, the reaction will be excessive, and the excess product will make it impossible to achieve connection, which is also not conducive to the relief of residual stress. The results of Example 2 and Comparative Example 2 show that the connection strength is affected by the current density. If the current density is too large, excessive intermetallic compounds will be generated, which is not conducive to the relief of residual stress and effective connection.

Claims

1. An intermediate layer connecting material of yttria transparent ceramic and metal, It is characterized in that The intermediate layer connecting material includes a hard metal intermediate layer, a composite intermediate layer or a soft metal intermediate layer starting from the yttrium oxide transparent ceramic side; the hard metal intermediate layer is selected from Ti and Cr, the soft metal intermediate layer is selected from Ni and Al, and the composite intermediate layer is selected from Ti / Ni, Ti / Al, Cr / Ni or Cr / Al.

2. The intermediate layer connecting material according to claim 1, It is characterized in that The thickness of the hard metal intermediate layer is 400-800nm, the thickness of the soft metal intermediate layer is 400-800nm; and the thickness of the composite intermediate layer is 600-800nm.

3. The intermediate layer connecting material according to claim 2, It is characterized in that The thickness of the hard metal intermediate layer in the composite intermediate layer is 300-400 nm, and the thickness of the soft metal intermediate layer is 300-400 nm.

4. The intermediate layer connecting material according to any one of claims 1 to 3, It is characterized in that The room temperature flexural strength of the yttrium oxide transparent ceramic is ≥150MPa, the elastic modulus is ≥160GPa, and the optical transmittance at a wavelength of 1050nm is not less than 80%.

5. A method for alleviating residual stress of electric field-assisted quick connection of yttria transparent ceramic and metal by an intermediate layer connection material according to any one of claims 1 to 4, It is characterized in that include: (1) using a magnetron sputtering method to prepare an intermediate layer on the surface to be connected of the yttrium oxide transparent ceramic that has been pre-treated by grinding, polishing and ultrasonic cleaning; (2) The sample to be connected is assembled in the order of first electrode / yttrium oxide transparent ceramic / intermediate layer / metal / second electrode and placed in an electric field assisted diffusion bonding device. An axial pressure of 0.1 to 1 MPa is applied to the sample to be connected. The vacuum degree is ≤6×10 -3 Pa, heat it to 875-925℃ and apply an electric field to the sample to be connected through the electrode. When the current density reaches 1-5 mA / mm 2 Then, the power is continued to be supplied and the temperature is kept for 30 to 180 seconds, and finally the temperature is cooled to room temperature at a cooling rate of 3 to 5°C / min to obtain a yttrium oxide transparent ceramic / intermediate layer / metal connector.

6. The method according to claim 5, It is characterized in that The surfaces of the yttrium oxide transparent ceramic and the metal to be connected are ground and polished and ultrasonically cleaned in an ethanol solution to make the surface roughness Ra of the surface of the yttrium oxide transparent ceramic to be connected less than or equal to 0.1 μm and the surface roughness Ra of the surface of the metal to be connected less than or equal to 5 μm.

7. The method according to claim 5 or 6, It is characterized in that The metal is one of titanium-based alloy, iron-based alloy or Monel alloy; preferably, the metal includes TC4, 4J29, 4J33 or Monel400.

8. The method according to any one of claims 5 to 7, It is characterized in that In step (1), the magnetron sputtering method comprises: placing the pretreated yttrium oxide transparent ceramic into a magnetron sputtering sample chamber, evacuating the chamber to a vacuum of 0.05 to 0.1 Pa, and performing radio frequency cleaning on the surface of the yttrium oxide transparent ceramic to be sputtered for 2 to 5 minutes at a power of 75 to 85 W; then evacuating the sputtering chamber to a vacuum of 5×10 -3 ~8×10 -3 Pa and heat to 175-225°C, pre-sputter at a power of 200-250W for 5-10min, then open the target baffle and base rotation switch, and perform magnetron sputtering at a sputtering power of 200-250W.

9. The method according to any one of claims 5 to 8, It is characterized in that In step (1), the sputtering time of the hard metal intermediate layer is 20 to 40 minutes, the sputtering time of the soft metal intermediate layer is 20 to 40 minutes, the sputtering time of the hard metal intermediate layer in the composite intermediate layer is 15 to 20 minutes, and the sputtering time of the soft metal intermediate layer is 15 to 20 minutes.

10. The method according to any one of claims 5 to 9, It is characterized in that In step (2), the direction of the applied electric field is from the first electrode to the second electrode, that is, from the yttrium oxide transparent ceramic side to the intermediate layer and finally to the metal side.

Citation Information

Patent Citations

  • Method for relieving residual stress of ceramic and metal brazed joint

    CN108672965A

  • Optoelectronic device transparent optical window airtight sealing method

    CN108732708A

  • Solid-state phase change composite brazing filler metal based on yttria-stabilized zirconia and preparation method of solid-state phase change composite brazing filler metal

    CN114147388A

  • Gradient-connection three-dimensional prestressed ceramic composite armor and preparation method thereof

    CN114941964A

  • Bonded ceramic-metal article

    US5055361A